A Case Control Study on Physical Activity and Obesity among Adolescent Children in an Urban Area of Tamilnadu - Angeline Grace G; Shanthi Edward; Gopalakrishnan S (National Journal of Community Medicine, 2021)
Background: Physical activity has a crucial role in prevention of obesity. Adolescents are required to spend at least 60 minutes a day in physical activity. This Case control study compares physical activity pattern among obese and non-obese adolescent school children studying in an urban area of Tamilnadu.